Great Western railway electrification, UK: pantograph interface model boosts speed. Issue 6 (30th July 2020) - Baimpas, Nikolaos; Dearman, Peter; Warren, Simon; Leathard, Matthew; Glass, Brad; Keenor, Garry
Abstract : Overhead contact wires on electrified railways often have to deviate from their standard height to pass over road crossings or under overbridges. Long height transitions are usually needed to ensure safe and reliable operation, otherwise line speeds need to be restricted. This paper sets out how data analysis combined with advanced simulation of the dynamic interaction between pantograph and overhead contact line proved that a location on the Great Western railway electrification programme in the UK could operate at much higher line speeds despite having a very steep wire gradient. The modelled results for Steventon in Oxfordshire showed a strong correlation with physical testing, enabling line speeds to nearly double. This approach could be used in future electrification projects to achieve significant time and cost savings.